2016
DOI: 10.1016/j.gca.2016.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Paired stable isotopes (O, C) and clumped isotope thermometry of magnesite and silica veins in the New Caledonia Peridotite Nappe

Abstract: The stable isotope compositions of veins provide information on the conditions of fluid-rock interaction and on the origin of fluids and temperatures. In New Caledonia, magnesite and silica veins occur throughout the Peridotite Nappe. In this work, we present stable isotope and clumped isotope data in order to constrain the conditions of fluid circulation and the relationship between fluid circulation and nickel ore-forming laterization focusing on the Koniambo Massif. For magnesite veins occurring at the base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 66 publications
3
33
0
1
Order By: Relevance
“…While we cannot be definitive regarding fractionation and re-equilibration, our data agree well with recent studies where a near-surface, low-temperature, meteoricwater origin for ultramafic-hosted magnesites has been proposed (Oskierski et al 2012;Quesnel et al 2013Quesnel et al , 2016 and also in the classic work of O'Neil & Barnes (1971). Data fields from these studies are shown in Figure 9 for comparison with our values.…”
Section: Stable Isotopessupporting
confidence: 91%
See 2 more Smart Citations
“…While we cannot be definitive regarding fractionation and re-equilibration, our data agree well with recent studies where a near-surface, low-temperature, meteoricwater origin for ultramafic-hosted magnesites has been proposed (Oskierski et al 2012;Quesnel et al 2013Quesnel et al , 2016 and also in the classic work of O'Neil & Barnes (1971). Data fields from these studies are shown in Figure 9 for comparison with our values.…”
Section: Stable Isotopessupporting
confidence: 91%
“…The hydrothermal signature may be pre-and/or co-genetic with weathering, and while we cannot constrain temperatures attained in the past, the isotope data show that most of the Mg-(hydro)carbonates in this study formed (or re-equilibrated) at temperatures at or below 30 ˚C. This interpretation, supported by similar recent field case studies (Oskierski et al 2012;Quesnel et al 2013Quesnel et al , 2016) conflicts with earlier laboratory work (Hänchen et al 2008;Möller 1989;Sayles & Fyfe 1973;Stevula et al 1978) where magnesite does not precipitate until fluid temperatures are in the range 60-120 ˚C.…”
Section: Paragenesissupporting
confidence: 79%
See 1 more Smart Citation
“…Karbonátkiválások vizsgálatával meghatározható a törések és a vetők mentén mozgó fluidumok hőmérséklete, illetve a fluidum eredeti oxigénizotópos-összetétele (SWANSON et al 2012, BERGMAN et al 2013, LOYD et al 2013, CRUSET et al 2016, QUESNEL et al 2016. A töréskitöltő karbonátok ∆ 47 értékei geotermális rezervoárok hőmérsék -letének meghatározására is használhatóak (SUMNER et al 2015).…”
Section: Szerkezetföldtani Alkalmazásokunclassified
“…Due to its position right above the presumed major thrust system, the frontal part of the Peridotite Nappe may have undergone renewed tangential shear on this occasion. In line with this hypothesis, top‐to‐SW shearing along the serpentine sole of the Koniambo Massif involves synkinematic magnesite veins [ Quesnel et al ., , ] formed at temperatures of only ~30°C [ Quesnel et al ., ], which suggests that the thickness of the Peridotite Nappe had already been much reduced when this deformation occurred.…”
Section: Obduction Tectonics In New Caledoniamentioning
confidence: 99%